Pesan Dakwah tentang Motivasi Sedekah dalam Youtube Jusuf Hamka - Husna, Nurul; Abdullah, H.; Muktarruddin, Muktarruddin (AHKAM, 2023)
The aim of this research is to find out the da'wah messages on Jusuf Hamka's YouTube and how to motivate alms. This research uses a qualitative descriptive method which not only collects and compiles data but further analyzes and interprets or interprets the data. The results of the research show that the preaching message about the motivation for alms in Jusuf Hamka's YouTube is that as servants of Allah, never feel that you will become poor because you help other people, no matter how much wealth we spend in the way of Allah, we are sure that Allah will multiply it. The power of sadaqah will save human life, whenever and wherever you are able to continue giving charity in the path of Allah's religion. As humans, we must continue to be grateful for the blessings of Allah SWT, because if it were not from Allah, humans would be nothing, and one way to be grateful is by giving charity to those who need it more. As a human being, make your life useful for others, convince yourself to be successful in this world and the afterlife by increasing your charity. The alms motivation technique conveyed by Jusuf Hamka is through taxpayers, the obligation to pay taxes is like giving alms in Islamic teachings. The principle of taxation and alms is almost the same, namely setting aside a portion of assets to be given to people who are entitled to receive it. Selling Yellow Rice in this case opens a business aimed at helping other people. According to Jusuf Hamka, the motivation for Muslims to be successful and diligent in giving alms is that they must be rich but not rich through corruption, that is, they must be rich from the results of hard work.